Variability of human behaviour in outdoor public spaces, associated with the thermal environment - Waldron, Julie A.; Lawson, Glyn; Robinson, Darren; Cobb, Sue (2017)
This paper presents part of the outcomes of a programme of research into the influence of the thermal environment on human behaviour in an outdoor public seating area. The research was conducted during one month in summer, autumn and winter of 2015 and 2016. The data gathered consists in the conduct of people using a public square in Nottingham city centre, and measurements of the environmental conditions taken at that place. The data of Number of People and the Size of Groups of people, were analysed according with the thermal environment of the place. The results showed a strong significant correlation between Number of People and Globe Temperature_sun [r = .66, p < .001]. A multiple regression analysis found that the Number of People per minute in a public space can be predicted using the Globe Temperature_sun and the Wind Speed data of that place [R-square of .39, p < 0.001]. These prediction models can be used to forecast the occupancy of the place and the grouping of users under different environmental conditions. The results can assist the design of urban spaces by allowing testing their future use with predicted data of human behaviour. In addition, the data obtained will serve as a foundation for further research about the human behaviour in public spaces.